Benjamin Franklin, young printer - Stevenson, Augusta; Quigley, Ray. (New York London Aladdin Books Collier Macmillan, 1986)
A biography of the young Philadelphia printer who grew up to become a world-renowned author, diplomat, scientist, and inventor, and one of the founding fathers of the United States.
Reprint of the ed.: Indianapolis : Bobbs-Merrill, c1983. (Childhood of famous Americans series).
Published 1941 under title: Ben Franklin, printer's boy.
Keywords: Franklin, Benjamin -- 1706-1790 -- hildhood and youth -- Juvenile literature; Franklin, Benjamin -- 1706-1790.; Statesmen -- Biography -- Juvenile literature. -- United States; Printers -- Biography -- Juvenile literature. -- United States; Statesmen; Printers